Classroom Techniques To Develop Students' English Grammatical Knowledge: A Naturalistic Study At SMP Muhammadiyah 1 Surakarta. - NURKASANAH, SITI; , Prof. Dr. Endang Fauziati, M. Hum (2016)
SITI NURKASANAH. A320120119.CLASSROOM TECHNIQUES TO DEVELOP STUDENTS' ENGLISH GRAMMATICAL KNOWLEDGE: A NATURALISTICSTUDY AT SMP MUHAMMADIYAH 1 SURAKARTA. Research Paper.School of Teacher Training and Education. Muhammadiyah University of Surakarta. 2016. This study aims at describing (1) the types of classroom technique used by the teachers in teaching English at SMP Muhammadiyah 1 Surakarta, (2) the purpose of each classroom technique, (3) the teachers' role, (4)the students' role, (5) the role of instructional material in teaching learning process. The type of the research is descriptive qualitative research. The methods of collecting data in this study are observation, interview, and documentation. The results of this study are as follows: (1) the types of classroom technique used by the teachers to develop students' English skill especially grammatical knowledge for example: filling the blank, reading aloud, answering question, picture describing, drilling and presentation (2) the purposes of classroom technique make the students interested and enjoyed in learning English language, (3)the teachers have roles as controller, organizer, prompter, resource, tutor, observer and model, (4) the students have roles as planner, group, tutor, monitor and evaluator, (5) there are some materials used by English teachers such as English textbook, workbook, and dictionary. The conclusion of this research is that the English teachers at SMP Muhammadiyah 1 Surakarta used several classroom techniques in teaching learning process to develop the students' English skill especially grammatical knowledge. These classroom techniques make the students more active and creative especially in learning grammatical knowledge. Based on the results, classroom technique used by the teachers is very important to make the students enthusiastic, interested, and enjoyed the teaching learning process of English grammatical knowledge.